Implikasi Teori Operant Conditioning terhadap Perundungan di Sekolah - Andika Aprilianto; Alfin Fatikh (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2024)
Bullying at school is a serious problem in Indonesia. To overcome this problem, the theory of operant conditioning from B.F. Skinner can provide important insights. This article explores how operant conditioning theory can be applied to overcome school bullying. Bullying is aggressive behaviour carried out repeatedly to attack a weaker party. In operant conditioning, behaviour is influenced by its consequences, whether in the form of positive reinforcement, negative reinforcement, or punishment. Positive reinforcement increases the likelihood of a behaviour being used, while punishment reduces it. Operant conditioning principles can be applied to reduce bullying behaviour, such as providing positive reinforcement for good behaviour and strict consequences for bullying behaviour. Teachers are important in implementing this principle to create a safe school environment. Operant conditioning-based interventions such as social skills training and forming support communities can help change bullying behaviour. However, bullying involves many factors, so operant conditioning theory is only one perspective in overcoming this problem. A comprehensive approach is needed involving various strategies and stakeholders in the school.